2021
DOI: 10.3390/en14123457
|View full text |Cite
|
Sign up to set email alerts
|

Polymodal Method of Improving the Quality of Photogrammetric Images and Models

Abstract: Photogrammetry using unmanned aerial vehicles has become very popular and is already commonly used. The most frequent photogrammetry products are an orthoimage, digital terrain model and a 3D object model. When executing measurement flights, it may happen that there are unsuitable lighting conditions, and the flight itself is fast and not very stable. As a result, noise and blur appear on the images, and the images themselves can have too low of a resolution to satisfy the quality requirements for a photogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…It was also proved in [6] that the quality of the bathymetric SfM is highly sensitive to flow, turbidity, and color. Other factors can also affect the development of any photogrammetric products, such as specific atmospheric conditions affecting the quality of the photo radiometry [16]; blurs appearing on the images [17]; water surface reflections [18]; and sea state, sunglint, and solar elevation angles [19]. In [20], refraction issues are additionally raised.…”
Section: Introductionmentioning
confidence: 99%
“…It was also proved in [6] that the quality of the bathymetric SfM is highly sensitive to flow, turbidity, and color. Other factors can also affect the development of any photogrammetric products, such as specific atmospheric conditions affecting the quality of the photo radiometry [16]; blurs appearing on the images [17]; water surface reflections [18]; and sea state, sunglint, and solar elevation angles [19]. In [20], refraction issues are additionally raised.…”
Section: Introductionmentioning
confidence: 99%
“…The software is one of the most popular programs used in photogrammetry (mainly in short-range photogrammetry) [53]. Aside from standard functionalities (photogrammetric triangulation [27], digital surface/digital terrain model generation [54,55], georeferenced orthomosaic generation [56,57], 3D model generation and texturing [58]), it enables the use of Python and Java APIs, which allow for adapting the software to the user's needs, often dictated by its use for specialist analyses by scientists in the photogrammetry and teledetection fields [23,59,60].…”
Section: Data Acquisitionmentioning
confidence: 99%
“…The results of this work can be the basis for planning the distribution of F-points when it is impossible to manipulate additional lighting (as in the case of studies conducted with the purpose of monitoring external artificial light at night-ALAN) or to select or change the artificial lighting of objects constituting the subject of the study. It must be noted that the quality of a photogrammetric study is affected by many factors, the specific division of which can be found in paper [23]. The most important factors include: object shape and colour [24,25], image quality [26], used software, methods [22,27], used sensors [28], accuracy of support systems [29][30][31][32] and data fusion methods [33][34][35], sensor orientation [1] or even the sensor's temperature [36].…”
Section: Introductionmentioning
confidence: 99%
“…The radiometric quality of the images is affected by many factors such as exposure parameters and sensor properties, flight parameters, and external conditions [8]. There are three groups of factors that influence the quality of images and the whole photogrammetric process: procedures, technical elements, and numerical methods [9]. Procedures refer to parameters related to imagery data collection.…”
Section: Introductionmentioning
confidence: 99%
“…Platform vibrations (often caused by poor vibroisolation and lack of stabilizing gimbals) can cause image blur and a jello effect [16-Figure 1. A breakdown of factors influencing UAV image quality (based on [9]).…”
Section: Introductionmentioning
confidence: 99%